Climate-modulated range expansion of reef-building coral communities off southeast Florida during the late Holocene - Modys, Alexander B.; Oleinik, Anton; Mortlock, Richard A.; Toth, Lauren T.; Precht, William F. (Frontiers in Marine Science, 2022)
The Holocene reefs off southeast Florida provide unique insights into the biogeographical and ecological response of western Atlantic coral reefs to past climate change that can be used to evaluate future climate impacts. However, previous studies have focused on millennial-scale change during the stable mid-Holocene, making it difficult to examine shorter-term variability relevant to modern climate warming. Using uranium-series dating of newly discovered subfossil coral rubble deposits, we establish a new high-resolution record of reef development off southeast Florida across a period of variable climate during the late Holocene. Our results indicate that reef communities dominated by reef-building Acropora and Orbicella corals persisted in the nearshore environments off southeast Florida episodically between 3500 and 1800 years before present. This timing coincides with regional warming at the northern extent of the Atlantic Warm Pool, suggesting a likely link between regional oceanographic climate and high-latitude reef development in southeast Florida. These findings not only extend the record of reef development in southeast Florida into the late Holocene, but they also have important implications on the future range expansion response of high-latitude reef communities to climate change.